Improving Pronunciation Ability and Teaching Pronunciation for Student Through Listening English Song - Ana Widiyanti (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2019)
This article aims to know the pronunciation teaching process through an English song. Also to know the difficultness which students feel. Pronunciation is important for a student because to know what the meaning of the song we must pronoun the right word, as far as I know, what te different pronoun had different meanings whereas the word is the same. This article uses qualitative methods to take some samples in the first semester students of the English education program. Some sample pronoun some words that on the song what I choose the song